The Effects of Age-Based and Grade-Based Sampling on the Relative Standing of Countries in International Comparative Studies of Student Achievement - O'Leary, Michael ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 2000)
The investigation reported in this paper was prompted by discrepancies between the published outcomes from two international tests of science achievement: (1) the Second International Assessment of Educational Progress (IAEP2), administered in 1991; and (2) the Third International Mathematics and Science Study (TIMSS), administered in 1995. One finding was that while average science achievement for Irish 13-year-olds was reported to be at the low end of the distribution for the 20 participating countries in IAEP2, it was around the middle of the distribution for the 40 or so countries that participated in TIMSS in the early grades of secondary schooling. Initial comparisons suggested that there were also inconsistencies in outcomes for some of the 11 other countries that participated in both surveys, such as France, Portugal, and Switzerland. Analyses reveal that when sampling/population definition differences between the two surveys are accounted for, science achievement in Ireland was not at the low level suggested by initial interpretations of IAEP2 data but was closer to the levels reported in TIMSS. While the sampling issue did not fully account for discrepancies with respect to the IAEP2/TIMSS outcomes for some countries, it is argued that the findings outlined in this paper have a number of implications for policymakers using data from future international comparative studies of student achievement. (Contains 2 figures, 6 tables, and 23 references.) (Author/SLD)
ERIC Note: Paper presented at the Annual Meeting of the American Educational Research Association (New Orleans, LA, April 24-28, 2000).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Achievement; Achievement Tests; Adolescents; Age Differences; Comparative Analysis; Foreign Countries; Instructional Program Divisions; International Education; International Studies; Junior High Schools; Science Achievement; Science Tests; Sciences; Test Results; Ireland; Third International Mathematics and Science Study; Opinion Papers; Speeches/Meeting Papers